2023
DOI: 10.3390/w15132349
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking the Potential of Wastewater Treatment: Machine Learning Based Energy Consumption Prediction

Abstract: Wastewater treatment plants (WWTPs) are energy-intensive facilities that fulfill stringent effluent quality norms. Energy consumption prediction in WWTPs is crucial for cost savings, process optimization, compliance with regulations, and reducing the carbon footprint. This paper evaluates and compares a set of 23 candidate machine-learning models to predict WWTP energy consumption using actual data from the Melbourne WWTP. To this end, Bayesian optimization has been applied to calibrate the investigated machin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Research has shown that machine learning methods have been widely applied to energy consumption modeling [1,2] , such as electricity [3] , wastewater treatment [4] , complex networks [5] , sensor parameters [6] , and more. Of course, there are also many applications in neural networks.…”
Section: Related Researchmentioning
confidence: 99%
“…Research has shown that machine learning methods have been widely applied to energy consumption modeling [1,2] , such as electricity [3] , wastewater treatment [4] , complex networks [5] , sensor parameters [6] , and more. Of course, there are also many applications in neural networks.…”
Section: Related Researchmentioning
confidence: 99%
“…Random forest (RF) is an ensemble-based model and a classification model that adds voluntariness and the basic principle of bootstrap aggregation (bagging), which is a method of aggregating samples by learning bootstrap models several times in multiple decision tree models. Random forest has high accuracy among classification models [22,[36][37][38][39]. Random forest randomly extracts learning data based on the basic principle of bagging, independently constructs a decision tree, and generates a total of n-trees.…”
Section: Random Forestmentioning
confidence: 99%
“…The confusion matrix is true positive (TP) when an observed value is predicted as 1 and the model result is 1, false negative (FN) when the observed value is predicted as 1 and the model result is 0, and the observed value is 0. Predicting the model output value as 1 is called false positive (FP), and when the observed value is 0, predicting the model output value as 0 is called true negative (TN) [6,15,39].…”
Section: Evaluating the Predictive Power Of The Modelmentioning
confidence: 99%
“…Comprehending the energy consumption (EC) of a wastewater treatment plant (WWTP) is crucial for various reasons [1]. Efficient energy management plays a direct role in enhancing cost-effectiveness by facilitating optimal resource allocation and the potential for savings.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond financial implications, a grasp of EC knowledge contributes to environmental sustainability and sustainable development by mitigating the carbon footprint linked with elevated energy use. Precise energy data facilitate regulatory compliance, while well-informed infrastructure planning, benchmarking, and funding decisions draw advantages from this comprehension [1]. Transparent endeavors to manage EC not only enhance public perception but also foster community engagement, aligning WWTPs with responsible resource stewardship and sustainable practices.…”
Section: Introductionmentioning
confidence: 99%